Penerapan Pembelajaran Model Discovery Learning sebagai Inovasi untuk Meningkatkan Hasil Belajar Kimia - Noormaliana Noormaliana (Jurnal Studi Inovasi, 2023)
This study aimed to improve students' chemistry learning outcomes using the Discovery Learning model in the form of achieving learning objectives in the material of Chemical Equilibrium and Equilibrium Shifts. The research method used was Classroom Action Research (CAR) with two cycles and two meetings in each cycle. The activities carried out in each cycle were planning, action implementation, observation and interpretation, analysis and reflection. The participants in this study were 33 students of class XII IPA 3 MAN 3 Banjarmasin. From the results of this study, it can be concluded that the application of the Discovery Learning model was able to improve learning outcomes in Chemistry lessons. The increase in learning outcomes could be seen from the increase in the average pretest and posttest scores from 66,7 to 72,1. In cycle 2 there was also an increase in the average score from 78,5 to 88,8. From the comparison of the average posttest scores in cycles 1 and 2, there was a very significant increase in average results with a total of 16.7 points. That way, the Discovery Learning model can be used by teachers by preparing themselves to be good at motivating, guiding and directing students in completing learning.